Intrinsic ferroelectric hysteresis behaviours for heterostructures - Chew, Khian Hooi; Shin, F.G.; Ishibashi, Y. (2006)
Intrinsic ferroelectric hysteresis behaviours for a heterostructure of interface between two different ferroelectrics of second-order transition are studied using the Landau-Ginzburg theory. We show that the existence of interfacial coupling could lead to a new polarization reversal mechanism. A detailed description of the polarization reversal mechanism of the heterostructure is discussed based on the hysteresis loops and the spatial variation of polarizations under various electric field strengths. (c) 2006 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.